Effect of flotation and vegetal fining agents on the aromatic characteristics of Malvasia del Lazio (Vitis vinifera L.) wine. (4th August 2020) - Pettinelli, Stefano; Pollon, Matteo; Costantini, Lorenzo; Bellincontro, Andrea; Segade, Susana R; Rolle, Luca; Mencarelli, Fabio
Abstract: BACKGROUND: Flotation is a process to reduce the must turbidity after grape pressing. The use of fining agents to reduce the polyphenol content is essential for white wine, but their impact on volatile compounds must be considered. Malvasia del Lazio juice ( Vitis vinifera L.) was treated before flotation with animal gelatin (GEL), legume protein plus chitin (LEGCHIT), and legume protein plus yeast extract (LEGYEAST). The clarification efficiency, total polyphenols, and total proteins were determined in the grape must before and after flotation, as well as the volatile composition and sensory characteristics of the resulting wines. RESULTS: The LEGCHIT trial was the most efficient, it being the fastest and achieving the lowest turbidity values. The GEL trial was the slowest, showing grape must turbidity values similar to LEGYEAST but also the highest total protein content. The vegetal protein treatments caused a decrease in the concentration of volatile organic compounds (VOCs) with respect to gelatin, which resulted in a reduction of aroma intensity, particularly for fruity and floral notes, but also for green notes. Furthermore, LEGCHIT wines were appreciated by panelists for their greater body and reduced astringency perception. CONCLUSION: The use of legume protein combined with chitin as a fining agent for flotation is advantageous in terms of clarification efficiency for grape must. Furthermore, the wines obtained showed high perceived global quality, even though a higher loss (38% and 27% respectively for LEGYEAST and LEGCHIT) of VOCs occurred when compared with gelatin. © 2020 Society of Chemical Industry